2004
DOI: 10.1590/s0102-09352004000300017
|View full text |Cite
|
Sign up to set email alerts
|

Reverse transcription-polymerase chain reaction assay for rabies virus detection

Abstract: [Protocolo de reação em cadeia pela polimerase precedida de transcrição reversa para a detecção de vírus da raiva]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
3
0
2
Order By: Relevance
“…It has been made possible to establish a definitive diagnosis by RT‐PCR from decomposed samples that may not be suitable for histology or virus isolation. The few studies undertaken to compare results obtained with RT‐PCR with those obtained using FAT and RT‐PCR showed that the RT‐PCR method was as good as the standard methods of antigen detection and virus isolation (Heaton et al., 1997 and Dantas Junior et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It has been made possible to establish a definitive diagnosis by RT‐PCR from decomposed samples that may not be suitable for histology or virus isolation. The few studies undertaken to compare results obtained with RT‐PCR with those obtained using FAT and RT‐PCR showed that the RT‐PCR method was as good as the standard methods of antigen detection and virus isolation (Heaton et al., 1997 and Dantas Junior et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…All bat brains were tested for lyssavirus by using reverse transcription PCR ( 8 ) and for lyssavirus antigens by using a direct fluorescence antibody test ( 9 ) using fluorescein isothiocyanate–conjugated monoclonal antibodies (Fujirebio Diagnostic, Inc, Malvern, PA, USA). The mouse inoculation test was conducted by using brains of 13 bats that died during capture and transport ( 9 ).…”
mentioning
confidence: 99%
“…The currently used Gold standard methods used for rabies diagnosis, the Fluorescence Antibody Test (FAT) and the Mouse Inoculation Test (MIT) are time consuming and are highly variable in specificity and sensitivity in the quantification assays. In this connection, the use of the RT-PCR for rabies virus detection was proposed [9] which proved to be a suitable technique for rabies diagnosis by various researches [10][11][12]. RT-PCR assays are used for the detection of Lyssavirus RNA from the samples like saliva, nuchal skin biopsy, eye washes etc with low viral load [13].…”
Section: Issn: 2638-1966mentioning
confidence: 99%